Physical punishment in childhood : the rights of the child - Saunders, Bernadette J.; Goddard, Chris [ (Christopher)] , 1947- (Wiley-Blackwell, 2010)
"Physical Punishment in Childhood explores the fine line between normalized physical punishment and illegal or unacceptable physical and emotional abuse of children. It presents important insights into this controversial issue from children, parents, grandparents and professionals who work with children. The authors reflect upon the status of children in societies that sanction physical punishment, the motivations and justifications for its use, perceptions of its effectiveness, and its impact; they also explore the power of the language used by parents, professionals and the media to describe physical punishment." "This book will be of value to child protection workers, children's legal representatives and practitioners, police officers, family court counsellors, psychologists who come into contact with children and families, those working in schools and pre-schools, and medical pract itioners who treat children and identify child abuse."--BOOK JACKET